(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article provides information on the nematode fauna found in the agricultural crops in the foothills. The specificity of the nematode fauna in tomato, carrot and sunflower crops is substantiated. It was determined that the diversity of cultivated crops affects the taxonomic composition and quantitative density of nematodes. The highest rate of biodiversity was observed in 48 species (528 ind.) in the roots and rhizosphere of long-term-planted-tomatoes, the soil of which is fine loamy in terms of their mechanical composition. In the fields with crop rotation, the number of nematodes was slightly lower, ie 45 species (499 ind.) in tomatoes planted after wheat, 39 species (479 ind.) in carrots, 33 species (357 ind.) in sunflowers grown in medium loamy soils and 28 species (247 ind.) in sunflowers cultivated in coarse loamy soils. The occurrence of nematode fauna in the agricultural crops is explained by the application of agro-technical measures to crops, the cultivation of the same crops in the long run, soil properties and other reasons. The distribution characteristics of nematodes in the soil of roots and the rhisophera, as well as their trophic relationship with plants were revealed. Moreover, dominant species of nematodes found in crops have also been identified. True parasitic nematode species, such as, Bitylenchus dubius, Merlinius bogdanovi-katjkovi, Helicotylenchus multicinctus, H. buxophilus, H. nannus, Pratylenchus pratensis, Ditylenchus dipsasi, Meloidogyne hapla have been identified in foothills.